MHC-I provides both quantitative resistance and susceptibility to blood parasites in blue tits in the wild - Rivero-de-Aguilar, J. (2016)
Major histocompatibility complex (MHC) genes are central for the adaptive immune response against parasites. Here, we investigated potential associations among MHC-I alleles and blood parasite infections in a natural breeding population of a passerine bird, the blue tit Cyanistes caeruleus, in central Spain. We screened both infection status (presence/absence of infection) and infection intensity to the pathogenic blood parasites Haemoproteus and Leucocytozoon. Three MHC-I alleles (UA104, UA108 and UA117) were associated with higher or lower infection intensities by Leucocytozoon. Interestingly, these associations were dependent on age and were found both among young and adult birds. No MHC alleles were associated with infection intensity by Haemoproteus parasites. In addition, no significant relationships were detected between infection status by Haemoproteus and Leucocytozoon infections and MHC alleles. The very high prevalence of these two parasites in our study population (79–100%) poses challenges to identify associations with infection status and also suggests that clearance of infections may be rare. In conclusion, associations between specific MHC-I alleles and Leucocytozoon parasites were related to either high or low infection intensities, and hence increased susceptibility or resistance to infection. © 2016 The Authors